Deskripsi Penalaran Analogi Ditinjau dari Tipe Kepribadian David Keirsey Siswa SMP Negeri 1 Ajibarang - Sugeng Widiyatmoko (AlphaMath : Journal of Mathematics Education, 2018)
This study aimed to describe students' analogical reasoning in SMP Negeri 1 Ajibarang viewed from personality types in the material of Three-Dimensional Shapes with Flat surfaces. Data subjects in this study were students of class VIII E and the sample was taken using purposive sampling technique. Students are grouped into three categories based on David Keirsey personality types namely rational, artisan, and guardian personality. Data were collected through tests, interviews, and documentation. To analyze the research data descriptive qualitative research method which included data reduction, data presentation, and conclusion was used.  In addition, echnical triangulation test was employed as a validation test of the results.  The results indicated that, based on analogical reasoning ability, it was seen that rational students mastered all indicators of analogical reasoning ability, i.e. encoding, inferring, mapping, and applying. Students with artisan personality type mastered the encoding indicator only. And guardian students were able to master the encoding, inferring and applying indicator.